Cooperation in the field of education and science (From the experience of Kazakhstan and Turkey) - Shauenova Г.А.; Buteev Б. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2018)
The article will focus on cooperation between the Republic of Kazakhstan and the Republic of Turkey in the field of education and science. It is based on the exchange of experience between the two countries on the principle of studying research in the field of the Kazakh language, literature and journalism in Turkey. In fraternal Turkey for the period from 1985 to 2017 a bibliographic index of protected research works was compiled, expert evaluation of the collected labor was carried out, the results are shown in tables, diagrams, drawings